Problems Faced by Grade XI Students in Speaking English at SMA Negeri 2 Sigi - Khusnul Khusnul; Mashuri Mashuri; Mochtar Marhum; Mawardin Mawardin (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This research aims to identify the problems faced by eleventh-grade students in speaking English. This research used a qualitative descriptive method, using questionnaires and interviews to collect data. The subject of this research was eleventh-grade students of SMA Negeri 2 Sigi. There are 44 students as participants. The researcher found that students' problems in speaking English are influenced by two factors: linguistic and psychological problems. Linguistic problems consist of a lack of vocabulary, poor grammar, a lack of pronunciation, and a lack of fluency. The dominant problem with a high percentage is fluency in speaking English. Other problems include linguistic problem in speaking, consisting of inhibition, nothing to say, a low number of participants, mother tongue use, and the dominant problem with a high percentage is mother tongue use.  While psychological problems consist of fear of making mistakes, shyness, anxiety, lack of confidence, and lack of motivation, the dominant problems with a high percentage are fear of making mistakes and lack of confidence. This research provides insights into the problems faced by eleventh-grade students in speaking English. It emphasizes the need to address these issues in the classroom to enhance students' learning experience.